2008
DOI: 10.1021/jp807723j
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Liquid Crystal Sol Containing Capped Ag−Pd Bimetallic Nanoparticles and Their Electro-Optic Properties

Abstract: Liquid crystal molecule-capped Ag−Pd bimetallic nanoparticles (atomic ratio = 1/9, 1/4, 1/1, 4/1, and 9/1) were prepared by photoirradiation of the tetrahydrofuran solution of silver perchlorate and palladium(II) acetate in the presence of liquid crystal molecule, 4′-pentylbiphenyl-4-carbonitrile. (5CB is often used for this compound based on conventional nomenclature 4′-pentyl-4-cyanobipenyl. Thus, 5CB is used in this paper.) The prepared bimetallic nanoparticles had an average diameter of 1.8−3.6 nm. Infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…The chemical method involves simultaneous or coreduction, successive or two‐step reduction of two kinds of metal ions, and “self‐organization” of bimetallic nanoparticles by physically mixing two kinds of already‐prepared monometallic nanoparticles with or without after treatments. Previously, we reported 4′‐pentyl‐4‐cyanobiphenyl (5CB)‐protected Ag/Pd bimetallic nanoparticles by the photoirradiation of the tetrahydrofurane solution of silver perchlorate and palladium(II) acetate in the presence of a liquid crystal molecule . Infrared spectra of carbon monoxide adsorbed on the bimetallic nanoparticles suggested that bimetallic nanoparticles had a random alloy structure.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical method involves simultaneous or coreduction, successive or two‐step reduction of two kinds of metal ions, and “self‐organization” of bimetallic nanoparticles by physically mixing two kinds of already‐prepared monometallic nanoparticles with or without after treatments. Previously, we reported 4′‐pentyl‐4‐cyanobiphenyl (5CB)‐protected Ag/Pd bimetallic nanoparticles by the photoirradiation of the tetrahydrofurane solution of silver perchlorate and palladium(II) acetate in the presence of a liquid crystal molecule . Infrared spectra of carbon monoxide adsorbed on the bimetallic nanoparticles suggested that bimetallic nanoparticles had a random alloy structure.…”
Section: Introductionmentioning
confidence: 99%
“…Many colloidal particles in nematic LCs having complex self-assembled structures, resulted from nematic-mediated anisotropic interaction between the particles, have been widely studied [3,4]. Nematic LCs are particularly interesting because of their coupling ability with external electric and magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of physical properties of liquid crystals by doping nanomaterials has received much attention from the view point of the enhancement of the performance of LCDs. Reflecting these trends several research groups reported on heterogeneous liquid crystal suspensions using; ferroelectric nanoparticles [1], ferromagnetic particles [2], fullerene [3], carbon nanotubes [4], diamond powders [5], metal nanoparticles [6,7], and metal nanorods [8]. In particular, strong activities have been reported for barium titanate (BaTiO 3 ) nanoparticles doped in nematic liquid crystalline mixtures [9].…”
Section: Introductionmentioning
confidence: 99%